ENCAPSULATION OF PLANT GROWTH-PROMOTING BACTERIA USING VERMICAST AND COW MANURE FOR BASIL PLANT (Ocimum basilicum) GROWTH AND PLANT NUTRIENT ENHANCEMENT - Amzar Fahmi Badarudin; Nur Maizatul Idayu Othman; Nazhatul Syahirah Sulaiman; Alif Farhan Shaharudin; Norazlina Abu Sari; Nur Qursyna Boll Kassim; Nur Badriyah Kamarulzaman, (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
Enterobacter sp. bacteria was successfully selected from UITM Pathology lab collection with the specific characteristic which is IAA production, and phosphate solubilization, nitrogen fixation test, siderophore production, and cellulose degradation. The selection of Enterobacter sp. was referred from the potential amount of IAA production that suitable for basil plants that rich with chemical compositions. The bacteria was entrapped as a potential of plant growth-promoting bacteria that consisted with sodium alginate solution, vermicast and cow manure. The bacteria population for all encapsulation of biofertilizer is range from 10^8-10^14.Vermicast and cow manure is act as carriers for the bacteria that has potential in a long lifespan. Three treatments which are encapsulated of vermicast, encapsulated of vermicast and cow manure, and encapsulated of vermicast and cow manure with PGPB were observed for the plant growth such as plant height (shoot length),number of leaves and plant nutrient enhancement of (Ocimum basilicum). This study observed that the treated plants with encapsulated PGPR with vermicast and cow manure showed the positive impacts on the growth and plant nutrient compared to control plants. Encapsulation technique is used as the method for entrap the bacteria with the carrier.